2019
DOI: 10.1111/eip.12857
|View full text |Cite
|
Sign up to set email alerts
|

Addressing mental health in elite athletes as a vehicle for early detection and intervention in the general community

Abstract: Recent scientific literature in addition to increased media attention has highlighted the important role of mental health in elite athletes. Often defined by terms such as “mental toughness”, athletes are now becoming more open to discussing the role of anxiety, depression and other psychologically distressing processes that are intertwined with their time both during and after elite sport. In line with this, recent international position statements regarding the mental health of athletes have been released. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…20 Another study suggested that in addition to sport-specific interventions for athletes, a better understanding of specific needs of the athlete and availability of good treatment may create a follow-on effect of increased help-seeking behaviour. 21 Difference in pretest and post-test In our study, professional footballers showed an increased help-seeking attitude and intentions and an increased confidence level in helping someone experiencing mental health symptoms after viewing the mental health awareness video. While these differences between pretest and post-test were statistically significant, it is worth mentioning that the increase in post-test scores was limited: +1.3 for attitude towards help-seeking (scale from 0 to 30), +1.3 for help-seeking intentions (scale from 11 to 77) and +0.6 for confidence level (scale from 0 to 16).…”
Section: Attitude Help-seeking Behaviours and Confidencementioning
confidence: 56%
See 1 more Smart Citation
“…20 Another study suggested that in addition to sport-specific interventions for athletes, a better understanding of specific needs of the athlete and availability of good treatment may create a follow-on effect of increased help-seeking behaviour. 21 Difference in pretest and post-test In our study, professional footballers showed an increased help-seeking attitude and intentions and an increased confidence level in helping someone experiencing mental health symptoms after viewing the mental health awareness video. While these differences between pretest and post-test were statistically significant, it is worth mentioning that the increase in post-test scores was limited: +1.3 for attitude towards help-seeking (scale from 0 to 30), +1.3 for help-seeking intentions (scale from 11 to 77) and +0.6 for confidence level (scale from 0 to 16).…”
Section: Attitude Help-seeking Behaviours and Confidencementioning
confidence: 56%
“… 20 Another study suggested that in addition to sport-specific interventions for athletes, a better understanding of specific needs of the athlete and availability of good treatment may create a follow-on effect of increased help-seeking behaviour. 21 …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous academic knowledge and clinical experience of a general population [ 43 ], which may be replicated in athletes, including rugby players [ 44 , 45 ]. Based on expert opinion [ 46 , 47 ], the fact that players in need of mental health support tend not to seek help or receive support with their problems should be shared among players, their coaches, health professionals, and others who work with players.…”
Section: Discussionmentioning
confidence: 99%
“…Organized recreational sports have several unique advantages as vehicles for the delivery of mental health programs, most notably including high participation rates globally (Aubert et al, 2018;Hulteen et al, 2017). The significant influence of sports stars in speaking about mental health (Walton et al, 2019) can also be leveraged through organized recreational sports. Indeed, a number of programs exist around the world that currently leverage such advantages, including: New Zealand Rugby's Headfirst program (headfirst.co.nz); Tackling the Blues run by Everton in the Community (evertonfc.com/ community/health-and-wellbeing/the-projects/tackling-the-blues); and, the State of Mind Ireland program (stateofmindireland.com/) as just a few examples.…”
Section: The Role Of Recreational Sports In Mental Health Promotionmentioning
confidence: 99%